The Effectiveness of Integrated Systemic Couple Therapy on Marital Differentiation and Marital Burnout of Couples Affected by Extramarital Affairs - Abolhasani, Sara; Ghorban Shiroudi, Shohreh; Zarbakhsh Bahri , Mohammadreza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This research aimed to determine the effectiveness of integrated systemic couple therapy on differentiation and marital disillusionment in couples affected by extramarital relationships. Method: The study employed a quasi-experimental design with pre-test, post-test, and follow-up stages, along with a control group. The statistical population consisted of women affected by extramarital relationships who sought counseling in Babol city centers during the first nine months of 2019. Thirty individuals were selected through convenience sampling and randomly assigned into two groups of fifteen for the experimental and control groups, respectively. The experimental group underwent Feldman's (1990) integrated systemic couple therapy protocol in twelve 90-minute group sessions, while the control group did not receive any training. Data were collected using the Pines' (1996) Marital Boredom Scale and the Skowron and Friedlander (1989) Differentiation of Self Inventory. Data were analyzed using repeated measures tests. Results: Results indicated that integrated systemic couple therapy had a significant effect on differentiation (F = 30.01, p < 0.001) and marital disillusionment (F = 78.86, p < 0.001) in women affected by extramarital relationships at the post-test stage. Additionally, the effectiveness of integrated systemic couple therapy on differentiation and marital disillusionment was sustained at the follow-up stage (p < 0.05). Conclusion: Given the findings, this research suggests that group-based integrated systemic couple therapy can aid in improving differentiation and marital disillusionment in women affected by extramarital relationships.